Neuromuscular comorbidity, atrial fibrillation and left bundle branch block predict the prognosis of left ventricular hypertrabeculation/noncompaction. (25th November 2020) - Stoellberger, C; Hasun, M; Winkler-Dworak, M; Finsterer, J
Abstract: Background: The prognosis of patients with left ventricular hypertrabeculation/noncompaction (LVHT) is controversially assessed. LVHT is frequently associated with neuromuscular disorders (NMDs). Aim of the study was to assess cardiac and neurological findings as predictors of mortality in LVHT-patients. Methods: Included were patients with LVHT diagnosed between June 1995 and December 2019 in one echocardiographic laboratory. They underwent a baseline cardiologic examination and were invited for a neurological investigation. In January 2020, their survival status was assessed. Results: LVHT was diagnosed in 310 patients (93 female, aged 53±18 years) with a prevalence of 0.4%/year. A neurologic investigation was performed in 205 patients (67%). A specific NMD was found in 33 of the investigated patients (16%), NMDs of unknown etiology in 123 (60%) and the neurological investigation was normal in 49 (24%) patients. During 86 months of follow-up, 59 patients received implanted electronic devices (cardioverter/defibrillator n=21, antibradycardic pacemakers n=11, cardiac resynchronization device/defibrillator n=22, cardiac resynchronization device n=4). During follow-up 105 patients died and 6 patients underwent heart transplantation. The mortality was 4.7%/year. By multivariate analysis, the following baseline parameters were identified as predictors of mortality: increased age (p=0.0005), inpatient-status when LVHT was diagnosed (p=0.0050), presence of a specific NMD (p=0.0187) or NMD of unknown etiology (p=0.0052), atrial fibrillation (p=0.0007) and left bundle branch block (p=0.0168). Conclusions: LVHT patients should be systematically investigated neurologically since neurological comorbidity has a prognostic impact. Electrocardiographic abnormalities like atrial fibrillation and left bundle branch block should be considered when planning pharmacotherapy and device-therapy. It has to be assessed by prospective studies, which measures improve the prognosis of LVHT. Funding Acknowledgement: Type of funding source: None